Faktor-Faktor yang Mempengaruh Keputusan Pembelian Konsumen Sepeda Motor Yamaha - Heri Sasono; Zainuddin Siata (Jurnal Penelitian Ekonomi Manajemen dan Bisnis, 2022)
Motorcycles are a means of transportation that are in demand by the people of Indonesia and the price is affordable so that the number continues to increase from year to year. This study aims to see what factors influence the decision to purchase a motorcycle, especially Yamaha. The research method uses Validity, Reliability, Normality Test, t Test, F Test (Anova), Regression Correlation and Multiple Linear Analysis. The total population is 1,801 people and the sample taken is 100 respondents who have made a purchase. Processing of research data using SPSS version 23 software. The results of the study are (a). Price and product quality variables have a significant effect on purchasing decisions. (b). Brand Image and Promotion variables have no significant effect on Purchase Decision. While the variable price, brand image, promotion and product quality simultaneously have a significant effect on purchasing decisions Yamaha